Experimental and numerical studies for the air cooling of fresh cauliflowers. (5th June 2018) - Le Bideau, P.; Noel, H.; Yassine, H.; Glouannec, P.
Highlights: The air-cooling of fresh cauliflowers is studied. A simple numerical model predicts the product temperatures and the water losses. The modelling approach takes into account the heterogeneities of the vegetable. The numeral results reveal a good agreement with the measurements. Abstract: The fresh vegetable farm produce needs to be cooled after the harvest before the shipment and the sale. The cooling duration is very sensitive to several parameters: foodstuffs nature (size, weight, properties), harvest period, packaging shapes, climatic conditions … In this paper, experimental and numerical investigations focused on forced air-cooling and room cooling of fresh cauliflowers are presented. For this vegetable, the optimal storage conditions are 4–7 °C and 90–98% relative humidity. As cauliflower is a voluminous (15–20 cm diameter) and heavy vegetable (600 g to more than 2000 g), the cooling process lasts generally several hours (>10 h) in the case of conventional room cooling. In order to apprehend the cooling kinetics of these products, some experiments carried out on a laboratory experimental set-up and on industrial site are presented. A 1D numerical model is firstly implemented to predict the temperature field and the mass loss of a single product. Several heat transfer mechanisms occur at the surface: convection, evaporation and long-wavelength infrared radiation. Based on in-situ experiments during which product temperature, air temperature and hygrometry were monitored, a second model is developed to simultaneously determine the temperature and the mass loss of several products placed in conventional room cooling. Comparisons between simulations and experiments show relevant results.